Exploiting Folding and Degradation Machineries To Target Undruggable Proteins: What Can a Computational Approach Tell Us?. (18th February 2021) - Serapian, Stefano A.; Triveri, Alice; Marchetti, Filippo; Castelli, Matteo; Colombo, Giorgio
Abstract: Advances in genomics and proteomics have unveiled an ever‐growing number of key proteins and provided mechanistic insights into the genesis of pathologies. This wealth of data showed that changes in expression levels of specific proteins, mutations, and post‐translational modifications can result in (often subtle) perturbations of functional protein–protein interaction networks, which ultimately determine disease phenotypes. Although many such validated pathogenic proteins have emerged as ideal drug targets, there are also several that escape traditional pharmacological regulation; these proteins have thus been labeled "undruggable". The challenges posed by undruggable targets call for new sorts of molecular intervention. One fascinating solution is to perturb a pathogenic protein's expression levels, rather than blocking its activities. In this Concept paper, we shall discuss chemical interventions aimed at recruiting undruggable proteins to the ubiquitin proteasome system, or aimed at disrupting protein‐protein interactions in the chaperone‐mediated cellular folding machinery: both kinds of intervention lead to a decrease in the amount of active pathogenic protein expressed. Specifically, we shall discuss the role of computational strategies in understanding the molecular determinants characterizing the function of synthetic molecules typically designed for either type of intervention. Finally, we shall provide our perspectives and views on the current limitations and possibilities to expand the scope of rational approaches to the design of chemical regulators of protein levels. Abstract : Molecules that block the pathogenic activities of otherwise undruggable proteins by decreasing their cell levels can be designed by using computational approaches. This can be achieved by forcing the recruitment of a ubiquitylation system to favor UPS degradation or by blocking the interactions of proteins with the chaperone machineries, thereby ensuring correct folding to the active structure.